2021
DOI: 10.3389/fnhum.2021.623315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation (tDCS) on Cognitive Performance and Cerebral Oxygen Hemodynamics: A Systematic Review

Abstract: Background: There is increasing evidence to support the efficacy of transcranial direct current stimulation (tDCS) applications in cognitive augmentation and rehabilitation. Neuromodulation achieved with tDCS may further regulate regional cerebral perfusion affiliated through the neurovascular unit; however, components of cerebral perfusion decrease across aging. A novel neuroimaging approach, functional near-infrared spectroscopy (fNIRS), can aid in quantifying these regional perfusional changes. To date, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 83 publications
(116 reference statements)
0
7
0
Order By: Relevance
“…Most studies using tDCS on human participants tend to report small effect sizes [57][58][59]. Interestingly, we observed that the Cohen's d effect sizes of TN-DCS on hippocampal activity ranged between 0.19 and 0.53, with the mean being 0.26.…”
Section: Tn-dcs Effect Sizesmentioning
confidence: 66%
“…Most studies using tDCS on human participants tend to report small effect sizes [57][58][59]. Interestingly, we observed that the Cohen's d effect sizes of TN-DCS on hippocampal activity ranged between 0.19 and 0.53, with the mean being 0.26.…”
Section: Tn-dcs Effect Sizesmentioning
confidence: 66%
“…During the VFT experiment, we used a 52-channel fNIRS device (ETG-4000 Optical Topography System) to estimate changes in regional cortical Hb concentration during the cognitive activation task, as described previously (55). The probes (17 emitters and 16 detectors, alternating) were fixed using 3 × 11 thermoplastic shells with an inter-optode distance of 3.0 cm.…”
Section: Functional Near-infrared Spectroscopy Signal Acquisitionmentioning
confidence: 99%
“…Interestingly, the literature enables us to make a connection between the processes underlying the reduction in aerobic performance due to hypoxia and the ones underlying the beneficial effect of tDCS on endurance performance. For instance, while hypoxia has been shown to impose cognitive and perceptual burden [ 30 ], reduce neurovascular coupling in the brain, and decrease the central drive to the periphery [ 31 , 36 ], tDCS can increase cognitive function [ 37 ], corticospinal excitability [ 1 , 38 ], motor unit recruitment [ 39 ], brain blood supply [ 40 ], reduce RPE, and improve exercise performance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%